A Corpus-Based Lexical Coverage of Coursebooks in Nigeria: A Case Study - Hamisu Hamisu Haruna; Azza Jauhar Ahmad Tajuddin; Ibrahim Bashir (Register Journal, 2024)
Since vocabulary is one of the most important components of reading comprehension, the relationship between the two has been studied in great detail. The significance of this relationship lies in the fact that learners' vocabulary size and the degree of coverage of the word families of the intended content are closely correlated with their ability to understand the context and the text. This study examined the lexical coverage of a corpus of 6,802,300 words from the first-year course books of the National Open University of Nigeria. With Anthony's AntWordProfiler software, we analyzed the lexical coverage of the corpus using the Lexical Frequency Profiling approach. The current study used Nation's (2012) BNC/COCA to determine the necessary vocabulary size for course book comprehension. The corpus study revealed that in order to reach 95% and 98% of the entire course book corpus, respectively, 5000 and 11000 word-families were required. However, vocabulary size needed for comprehension of each disciplinary field varied greatly, with the hard sciences having a significantly higher lexical demand as compared to the other fields. This means that students need a larger vocabulary to interact with and understand the course books, especially in the hard sciences. It therefore recommended that materials writers and instructors consider the specific disciplinary vocabulary needs in course books.  Similarly, due to disciplinary differences, more specific instructions and glossaries are needed for first-year university students to have a better understanding of course books, especially hard science course books. The study demonstrated the significance of corpus-based approaches in the analysis of language learning materials. Overall, the study underlined the importance of sufficient vocabulary for reading comprehension.